Compliance and use of the World Health Organization checklist in UK operating theatres. Issue 12 (9th October 2013) - Pickering, S. P.; Robertson, E. R.; Griffin, D.; Hadi, M.; Morgan, L. J.; Catchpole, K. C.; New, S.; Collins, G.; McCulloch, P.
<x xml:space="preserve">Abstract</x> Background The World Health Organization (WHO) Surgical Safety Checklist is reported to reduce surgical morbidity and mortality, and is mandatory in the UK National Health Service. Hospital audit data show high compliance rates, but direct observation suggests that actual performance may be suboptimal. Methods For each observed operation, WHO time‐out and sign‐out attempts were recorded, and the quality of the time‐out was evaluated using three measures: all information points communicated, all personnel present and active participation. Results Observation of WHO checklist performance was conducted for 294 operations, in five hospitals and four surgical specialties. Time‐out was attempted in 257 operations (87·4 per cent) and sign‐out in 26 (8·8 per cent). Within time‐out, all information was communicated in 141 (54·9 per cent), the whole team was present in 199 (77·4 per cent) and active participation was observed in 187 (72·8 per cent) operations. Surgical specialty did not affect time‐out or sign‐out attempt frequency (P = 0·453). Time‐out attempt frequency (range 42–100 per cent) as well as all information communicated (15–83 per cent), all team present (35–90 per cent) and active participation (15–93 per cent) varied between hospitals (P < 0·001 for all). Conclusion Meaningful compliance with the WHO Surgical Safety Checklist is much lower than indicated by administrative data. Sign‐out compliance is generally poor, suggesting incompatibility with normal theatre work practices. There is variation between hospitals, but consistency across studied specialties, suggesting a need to address organizational culture issues.